Sonographic assessment of changes in diaphragmatic kinetics induced by inspiratory resistive loading. Issue 3 (21st March 2013) - Soilemezi, Eleni; Tsagourias, Matthew; Talias, Michael A.; Soteriades, Elpidoforos S.; Makrakis, Vasilios; Zakynthinos, Epaminondas; Matamis, Dimitrios
<x xml:space="preserve">Abstract</x> M‐mode sonography is already being used to study diaphragmatic motion, but to our knowledge, there is no sonographic information regarding diaphragmatic kinetics under the influence of variable respiratory loads; this study examines the special sonographic features of diaphragmatic excursion pattern during inspiratory resistive loading.